Distributed Reactive Power Control With Adaptive Volt/VAr in Active Distribution Systems - Ozdemir, Hilal; Selim Turkoglu, A.; Erdinc, Ozan; Pisica, Ioana (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2026)
The rapid development of distributed generators (DGs) has increased the complexity of distribution system (DS), creating a need for advanced solutions to maintain operational constraints. This paper introduces a novel distributed decision-making algorithm that models DS operators and DGs as distinct entities, addressing the growing complexity of DSs while accounting for realistic operational constraints. The proposed approach utilizes the reactive power support of DGs to minimize energy curtailment through an adaptive piecewise Voltage/Reactive Power (Volt/VAr) control strategy. The proposed algorithm is tested on both the IEEE 33-bus test system and a real-world distribution network, which includes an existing battery-based energy storage system (BESS) and is extended with an electrolyzer to capture additional operational flexibility. This is achieved using Mixed-Integer Nonlinear Programming (MINLP) modeling, which identifies dynamic operating regions for smart inverters and ensures compliance with network requirements. This study contributes to the existing knowledge by addressing network complexity via modeling the DS operator and DGs as distinct entities, considering real-world limitations and privacy concerns, while also providing an adaptive Volt/VAr control strategy to enhance network performance and DG integration. The effectiveness of the proposed algorithm is demonstrated by a significant reduction in active power curtailment compared to default voltage settings.
Keywords: Artificial satellites; Earth Observing System; Flexible printed circuits; Printed circuits; Interoperability; Internetworking; Internet of Things; Electronic mail; Protocols; Communication systems; Distributed optimization; inverter-based resources; multi-agent systems; Volt/VAr control; VOLTAGE REGULATION; INVERTER; OPTIMIZATION; Computer Science; Engineering; Telecommunications